Bonding of different self-adhesive resins to high-strength composite resin block treated with surface conditioning. Issue 3 (July 2019) - Yu, Hao; Yoshida, Keiichi; Cheng, Hui; Sawase, Takashi
Abstract: Purpose: This study aimed to evaluate the effects of chemical conditioning and self-adhesive resins (SARs) on the bonding of mechanically conditioned high-strength composite resin block (HSCRB). Methods: Eighteen sections of HSCRB (KZR-CAD HR 3 Gammatheta, Yamakin) were treated with alumina air abrasion and randomly divided into 3 groups according to the SARs for bonding: RelyX Unicem 2 (RXU), SA Luting Plus (SAL), and G-Cem ONE (GCO). The sections were further divided into 3 subgroups according to the chemical conditioning of the adherend surfaces: no conditioning (C), universal adhesive (UA), and a mixture of γ-MPTS and 10-MDP (MM). After the surface conditioning, the sections were cemented with the SARs. Each cemented section was cut into 40 beams. Half of the beams were thermocycled (4 °C/60 °C, 10, 000 cycles). The micro-tensile bond strength (μTBS) values were measured using a universal testing machine. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), contact angles, and surface roughness measurements were performed on the adherend surfaces of each subgroup. Results: RXU showed the highest μTBS values among the 3 SARs tested, while MM application exhibited the highest μTBS values among the 3 chemical conditioning methods tested. After thermocycling, the samples in the RXU/MM, RXU/UA, and GCO/MM groups showed no significant changes in the μTBS values, whereas the others showed a significant reduction. Conclusions: The bond strength of HSCRB was influenced by the chemical conditioning, SARs, and aging. γ-MPTS and 10-MDP application yielded higher μTBS values of mechanically treated HSCRB than the UA.